HPLC determination of phenolic compounds content in Parmelia sulcata and Parmelia vagans thalli - O. A. Kyslychenko; Viktoriia V. Protska; Iryna O. Zhuravel (Pensoft Publishers, 2019)
The species of Parmelia genus have long been used in Indian folk medicine for the treatment of bronchitis, ulcers, furunculosis, cardiovascular diseases, urolithiasis, amenorrhea, and also at infectious and inflammatory diseases. In Ukraine, the most common lichens of the Parmelia genus are Parmelia sulcata Tailor and Parmelia vagans Nyl. At the same time, thalli of Parmelia genus lichens belong to the non-officinal and poorly studied types of raw material. The qualitative composition and the quantitative content of phenolic compounds in Parmelia sulcata and Parmelia vagans thalli was studied by HPLC. According to the results of the chromatographic analysis, salazinic, fumaroprotocetraric, usnic acids, chloratranorin and atranorin were identified in both types of raw material studied. In addition, protocetraric acid was identified in Parmelia sulcata thalli. According to the results of the experiment, the total content of identified phenolic compounds in Parmelia sulcata thalli was 2019.71±40.39 g/mol, and in Parmelia vagans thalli it comprised 1754.18±34.77 g/mol. In the thalli of both studied species of Parmelia genus, fumaroprotocetraric acid dominanted by the quantity. This substance was present in Parmelia sulcata thalli in the amount of 474.00±9.00 g/mol, and in Parmelia vagans thalli - 456.21±8.67 g/mol. In addition, a significant amount of chloratranorin (408.79±8.99 g/mol) was present in Parmelia sulcata thalli. Quite a high content of atranorin (393.34±8.65 g/mol) and usnic acid (375.31±7.53 g/mol) were defined in Parmelia vagans thalli. The results obtained can be used in the development of quality control methods for Parmelia sulcata and Parmelia vagans thalli, as well as medicines based on these types of raw materials.